“Influencia de un Plan de Ergonomía sobre lesiones musculoesqueléticas en el área metalmecánica de Skanska – Cajamarca” - Mendoza Anticona, David Luciano (2019)
ABSTRACT This actual researching has evaluated the influence of an ergonomics plan to reduce musculoskeletal injuries in metalworking works from Skanska Del Peru company - Yanacocha service Cajamarca, Period 2015-2016. The selection of specific work to evaluate the work area was performed. Task assessments conducted by Reba method, which allows the joint analysis of the positions taken by the upper limbs of the body (arm, forearm, wrist), trunk, neck and legs. In the part of field evaluation, the evaluation of hot works to obtain data in tables showing the angles and score tips to evaluate was made, for corrective measures how would the proper positions for the work and prevent and / or reduce musculoskeletal injuries. Photographs were taken and Reba method for the development of the results observed in the field was used. In the experimental part assessment welding it was performed according to experimental design developed doing to fullfil with the preventive actions mentioned in the Ergonomics Plan. The experimental results showed that, when applying the Ergonomics Plan, musculoskeletal injuries diminish, which are generated mainly by forced and inadequate positions carried out by the personnel and the lack of an awareness about the labor prevention and adaptation to their job to ergonomic measures.